2015
DOI: 10.1016/j.ijhcs.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrating knowledge of multitasking and interruptions across different perspectives and research methods

Abstract: Multitasking and interruptions have been studied using a variety of methods in multiple fields (e.g., HCI, cognitive science, computer science, and social sciences).This diversity brings many complementary insights. However, it also challenges researchers to understand how seemingly disparate ideas can best be integrated to further theory and to inform the design of interactive systems. There is therefore a need for a platform to discuss how different approaches to understanding multitasking and interruptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…On the other hand, it may be unsurprising, given that researchers in the quality improvement community focus on rapid translation of findings into practice through interventions that address interruptions. Some researchers have argued that interventions can be improved by combining different methodological approaches [184], but adopting methods or principles from other traditions may take too long or it may require an inappropriate focus on a very specific research question [87] or a level of control that is unachievable in practice.…”
Section: Implications For Interruptions Investigations In Healthcarementioning
confidence: 99%
“…On the other hand, it may be unsurprising, given that researchers in the quality improvement community focus on rapid translation of findings into practice through interventions that address interruptions. Some researchers have argued that interventions can be improved by combining different methodological approaches [184], but adopting methods or principles from other traditions may take too long or it may require an inappropriate focus on a very specific research question [87] or a level of control that is unachievable in practice.…”
Section: Implications For Interruptions Investigations In Healthcarementioning
confidence: 99%
“…First, we have described the experimental paradigm as a primary task that is periodically interrupted, but it could be described as task switching or task interleaving. As Janssen et al (2015) point out "interruptions are only one form of the perhaps broader category of multitasking" (p. 3). Below we note where our research is interruption-specific and where it has commonalities with multitasking research.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…One of these domains is healthcare environments, in which the practical problems of interruption lately have been receiving a great amount of attention (e.g. Janssen et al 2015;Sanderson and Grundgeiger 2015;Weigl et al 2014;Werner and Holden 2015).…”
Section: Upcoming Trends In Interruption Researchmentioning
confidence: 99%
“…However, DCog does not exclude the quantitative approach. In fact, Janssen et al (2015) suggested a combination of various methods and techniques to further develop interruption research. By gathering quantitative data such as the amount of interruptions during a certain time interval in combination with qualitative data regarding what kind of interruptions happening and how they are handled brings a broader perspective, which potentially could yield a richer description of the characteristics of naturally occurring interruptions, how frequent they are, and which cognitive strategies humans use to handle them.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation